First-principles investigation on site preferences and elastic properties of γ′-Pt3Al with ternary alloying elements X (X = Ni, Ru, Re) - Bixia Yao; Guanhua Qin; Ruiling Gao; Chao Liu; Rui Chen; Hui Zhang; Xi Li; Wei Ren (Journal of Materials Research and Technology, 2025)
In this study, the site preferences and elastic properties of γ′-Pt3Al doped with ternary alloying elements Ni, Ru, and Re were systematically investigated using first-principles calculations. The calculated equilibrium lattice parameters were in good agreement with previous experimental and theoretical values, validating the accuracy of our computational approach. The site occupancies of the ternary alloying elements in γ′-Pt3Al were predicted, revealing distinct preferences based on alloy composition and thermodynamic conditions. Specifically, Re was found to preferentially occupy the Al sublattice, whereas the preference of Ni and Ru for either Pt or Al sublattices depends on the composition and temperature. Structural distortion induced by the ternary alloying elements at Pt sites were observed, while their occupancy at Al sites stabilized the L12 structure of γ′-Pt3Al. Furthermore, the influence of the ternary alloying elements on the elastic properties of γ′-Pt3Al was evaluated by calculating elastic constants, bulk modulus, shear modulus, and Young's modulus. The analysis of elastic properties showed that alloys exhibit improved ductility when Ni, Ru, and Re occupy Al sites, exceeding their performance at Pt sites. The obtained results offer a profound understanding of site occupancy and mechanical behavior, crucial for the rational design and optimization of Pt-based alloys for diverse applications.